Co-producing ecosystem services for adapting to climate change - Lavorel, S.; Locatelli, Bruno; Colloff, Matthew J.; Bruley, E. (Royal Society, 2020)
Ecosystems can sustain social adaptation to environmental change by protecting people from climate change effects and providing options for sustaining material and non-material benefits as ecological structure and functions transform. Along adaptation pathways, people navigate the trade-offs between different ecosystem contributions to adaptation, or adaptation services (AS), and can enhance their synergies and co-benefits as environmental change unfolds. Understanding trade-offs and co-benefits of AS is therefore essential to support social adaptation and requires analysing how people co-produce AS. We analysed co-production along the three steps of the ecosystem cascade: (i) ecosystem management; (ii) mobilization; and (iii) appropriation, social access and appreciation. Using five exemplary case studies across socio-ecosystems and continents, we show how five broad mechanisms already active for current ecosystem services can enhance co-benefits and minimize trade-offs between AS: (1) traditional and multi-functional land/sea management targeting ecological resilience; (2) pro-active management for ecosystem transformation; (3) co-production of novel services in landscapes without compromising other services; (4) collective governance of all co-production steps; and (5) feedbacks from appropriation, appreciation of and social access to main AS. We conclude that knowledge and recognition of co-production mechanisms will enable pro-active management and governance for collective adaptation to ecosystem transformation.This article is part of the theme issue ‘Climate change and ecosystems: threats, opportunities and solutions’.